Mapping factors that support social integration of minangkabau community in Luhak Agam - Siti Fathimah; Fitri Eriyanti; Erianjoni (International Conferences on Educational, Social Sciences and Technology)
Domain origin of Minangkabau is divided into three Luhak known as Luhak Nan Tigo. This region is the center of Minangkabau cultures. The three Luhak are located in West Sumatera. Those areas also have a diversity of ethnicity, religious, and customs. This study aims to formulate the factors which support social integration of Minangkabau community. By using descriptive qualitative approach, the informants of this research are the elements of regional leaders, youth leaders, custom leaders, religious leaders and ordinary citizens. Techniques of data collection was observation, interviews, and documentation. The result of the research found that the strong traditions that still make Minangkabaupeople to feel a unity, their customary laws in Minangkabau region makes the people feel protected and not be afraid to break the rules of the customs. Customary laws become a life principle of social life at the same guidelines with the aim of creating security, discipline and creating a virtuous society and noble characters.